Community characteristics and relationship between gut microbiota and intratumoral microbiota in hepatocellular carcinoma - Lin, Huangpeng; Ma, Zexian; Li, Jin; Zhu, Heping; Huang, Xuefeng; Chen, Huimin; Tu, Liang; Lian, Yifan; Su, Yongjie (Frontiers in Immunology, 2025)
BackgroundThe combination of local therapy with lenvatinib and programmed cell death protein-1 (PD-1) inhibitors represents an emerging treatment paradigm for unresectable hepatocellular carcinoma (uHCC). Our study sought to investigate the interrelationship between gut microbiota and intratumoral microbiota in the context of triple therapy, with a view to identifying potential biological markers.MethodsThe gut microbial community profiles of patients with primary untreated hepatocellular carcinoma (HCC) and those treated with local therapy combined with lenvatinib and PD-1 inhibitors were analyzed by 16S rRNA gene amplicon sequencing. Additionally, microbial community profiles of tumor tissues of patients with HCC and normal liver tissues were analyzed.ResultsIn our investigation, we observed that patients with HCC who received triple therapy exhibited a notable enhancement in the abundance of Actinobacteriota and a considerable decrease in Escherichia Shigella. Patients who received hepatic artery infusion chemotherapy (HAIC) in combination with levatinib and PD-1 inhibitors exhibited significantly elevated levels of Faecalibacterium prausnitzii and Bacteroides stercoris in comparison to those who received transarterial chemoembolization (TACE) in combination with levatinib and PD-1 inhibitors. Furthermore, a notable decline in microbial diversity was observed within HCC tumors in comparison to normal liver tissues. The gut and intratumoral microbiota in HCC patients exhibited a high degree of similarity to the microbes present at the phylum level.ConclusionsGut microbiota is connected to triple therapy with local therapy combined with lenvatinib and PD-1 inhibitors for HCC. These discoveries underscore the potential of utilizing gut microbiota and intratumoral microbiota as biomarkers, as well as the possibility of triple therapy in the management of HCC.